2019
DOI: 10.1212/wnl.0000000000007038
|View full text |Cite
|
Sign up to set email alerts
|

FDG-PET patterns associated with underlying pathology in corticobasal syndrome

Abstract: ObjectiveTo evaluate brain 18Fluorodeoxyglucose PET (FDG-PET) differences among patients with a clinical diagnosis of corticobasal syndrome (CBS) and distinct underling primary pathologies.MethodsWe studied 29 patients with a diagnosis of CBS who underwent FDG-PET scan and postmortem neuropathologic examination. Patients were divided into subgroups on the basis of primary pathologic diagnosis: CBS-corticobasal degeneration (CBS-CBD) (14 patients), CBS-Alzheimer disease (CBS-AD) (10 patients), and CBS–progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
73
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(88 citation statements)
references
References 51 publications
14
73
0
1
Order By: Relevance
“…Moreover, a recent study with neuropathologic examination showed that CBS underlying pathologies are associated with different metabolic degeneration patterns and described hypometabolism for CBS-CBD, CBS-AD, and CBS-PSP 26 . The CBS-AD metabolic pattern described was similar to what we observed comparing patients with positive and negative PIB-PET.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moreover, a recent study with neuropathologic examination showed that CBS underlying pathologies are associated with different metabolic degeneration patterns and described hypometabolism for CBS-CBD, CBS-AD, and CBS-PSP 26 . The CBS-AD metabolic pattern described was similar to what we observed comparing patients with positive and negative PIB-PET.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the FDG-PET findings, the patients were split into two groups, namely "CBS likely related to AD" (CBS FDG-AD), or "CBS likely not related to AD" (CBS FDG-nonAD), according to patterns of hypometabolism previously described for neurodegenerative diseases. 18,19,21,[23][24][25][26] Hypometabolic pattern suggestive of AD included decreased regional brain glucose metabolism (rBGM) in the posterior temporoparietal, inferior temporal regions, precuneus, and posterior cingulate gyrus. 38,39 We considered the remaining patterns as non-AD group and performed a subclassification regarding these different patterns into CBD, PSP, frontotemporal dementia (FTD), Lewy Body dementia (LBD), and indeterminate (closely related to tauopathies), also according to patterns previously described.…”
Section: Fdg-petmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 6 , 39 ] In another 18 F-FDG PET imaging, the metabolism and perfusion of glucose in the asymmetric frontotemporal lobe and basal ganglia also decrease. [ 49 ]…”
Section: Significance Of Pet/spect Molecular Imaging In the Differentmentioning
confidence: 99%